Digitalization of rabbit farming in Medan City, Indonesia - Rulianda Purnomo Wibowo; Galih Ari Wirawan Siregar; Hayatunnufus Hayatunnufus; Muhammad Khaliqi; Herfita Rizki Hasanah Gurning (Talenta Publisher Universitas Sumatera Utara, 2025)
Rabbit farming is presently being developed as an alternative source of animal protein in Indonesia. Some of these challenges include the appropriate keeping of records related to production processes and the marketing of products. In response to the challenges encountered by rabbit farming group, a proposed solution entails offering training on the use of digital applications for financial bookkeeping and marketing purposes. This community service initiative is geared towards facilitating the implementation of an Android application aimed at enhancing the operational efficiency of rabbit farming businesses. The approach used in this community service is Participatory Rural Appraisal. The results of the Community Service activities indicated that the farmers were proficient in using the Adorabbit application and followed the instructions effectively. Based on this observation, the adorabbit application was inferred to provide significant assistance to rabbit farmers in Medan City, specifically in the areas of recording rabbit production and managing finances, thereby, enabling the enhancement and expansion of their livestock businesses.